2019
DOI: 10.24834/educare.2019.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Dramatisering i spänningsfältet mellan som om och som är och sexåringars meningsskapande av kemiska begrepp och processer

Abstract: In this study, we discuss dramatizing as a form of play-responsive teaching in early childhood education. Based on empirical observation, the purpose of the study is to contribute to knowledge-building through offering possibilities for children to make sense of scientific knowledge by engaging in mutual fantasizing about certain fundamental processes and concepts in chemistry. The empirical foundation consists of interviews conducted with eleven 6-year-old children after they had participated in a workshop at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…Åkerblom and Pramling [11] analyzed how six-year-olds reasoned about their experiences and how they understood the content after participating in a drama activity focusing on molecules at a culture center. The starting point for the project was to see how the children manage the relationship between imagination (as if) and scientific content (as it is).…”
Section: Previous Research 21 Children's Understanding Of Moleculesmentioning
confidence: 99%
See 1 more Smart Citation
“…Åkerblom and Pramling [11] analyzed how six-year-olds reasoned about their experiences and how they understood the content after participating in a drama activity focusing on molecules at a culture center. The starting point for the project was to see how the children manage the relationship between imagination (as if) and scientific content (as it is).…”
Section: Previous Research 21 Children's Understanding Of Moleculesmentioning
confidence: 99%
“…Between these poles (the world "as if" and "as it is"), a tension field was described, which the children dealt with by reasoning in different ways: pretending to be molecules, using familiar phenomena such as similes to reason about things that are challenging, coordinating "as if", but also taking part in what the drama teacher imagines. In summary, Åkerblom and Pramling [11] found that the children used linguistic resources that they could master at the time, such as similes, to approach the scientific content, which would otherwise have required other linguistic resources to reason about. The researchers discuss the children's navigation between "as if" (the fantasy used in the pretend world they use in their play and stories) and "which it is" (the real world they perceive through their senses in reality) in the same way scientific phenomena that children experience through their senses need to be described in a manner so that children can actually understand them.…”
Section: Previous Research 21 Children's Understanding Of Moleculesmentioning
confidence: 99%